The Influence of Leadership Style and Work Environment on Organizational Climate with Work Ethic as an Intervening Variable at the Belawan Harbormaster and Main Port Authority Office - Ardi Sahat Parasian; Kiki Farida Ferine (Equivalent : Journal of Economic, Accounting and Management, 2026)
This study aims to analyze the influence of leadership style and work environment on organizational climate, with work ethic as an intervening variable, at the Belawan Harbormaster and Main Port Authority Office. This research is motivated by the important role of leadership style and work environment conditions in shaping employee work ethic and creating a conducive organizational climate in an agency with a strategic function in the field of shipping safety and supervision. The study was conducted at the Belawan Harbormaster and Main Port Authority Office, located on Jalan Deli, Medan Belawan District, Zip Code 20411, starting in June 2025. The study population consisted of 244 employees, and the Slovin formula was used for sampling, resulting in a sample size of 151 respondents. Data collection was conducted through questionnaires, while data analysis employed a PLS-based Structural Equation Modeling (SEM) approach. The results indicate that leadership style and work environment have a positive and significant effect on work ethic and organizational climate. Furthermore, work ethic has been shown to have a positive and significant impact on organizational climate and mediate the relationship between leadership style and work environment. Overall, this study confirms that improving effective leadership styles and a supportive work environment can strengthen employee work ethic and create a better organizational climate.